2018
DOI: 10.1093/inthealth/ihy035
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sociodemographic factors and reporting having terminated a pregnancy among Ghanaian women: a population-based study

Abstract: Women who are employed, cohabit with a partner and are considered middle class or wealthy are more likely than their counterparts to report having terminated a pregnancy. Ghanaian women with intermediate levels of education are more likely than both their more- and less-educated counterparts to report having terminated a pregnancy. These findings highlight the need for the development of policies aimed at reducing unsafe abortions associated with unintended pregnancies. Specific recommendations include providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
5
11
0
Order By: Relevance
“…On the other hand, another study reported that the probability of having terminated pregnancy was higher for women in high socio-economic status [35]. Our study showed that the risk of terminated pregnancies increased with the increased wealth index, which is consistent with the existing literature among Nigerian women based on Nigerian DHS data [49] and Ghanaian women based on Ghana DHS data [18]. Since induced abortion is still illegal in Bangladesh except under certain circumstances, accessing induced abortion or menstrual regulation may be unaffordable for women in low economic status [50].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…On the other hand, another study reported that the probability of having terminated pregnancy was higher for women in high socio-economic status [35]. Our study showed that the risk of terminated pregnancies increased with the increased wealth index, which is consistent with the existing literature among Nigerian women based on Nigerian DHS data [49] and Ghanaian women based on Ghana DHS data [18]. Since induced abortion is still illegal in Bangladesh except under certain circumstances, accessing induced abortion or menstrual regulation may be unaffordable for women in low economic status [50].…”
Section: Discussionsupporting
confidence: 91%
“…The results from our study suggested that women who were involved in any occupation were at an increased risk of reported pregnancy termination in Bangladesh. This is consistent with another study conducted by in Ghanaian women based on Ghana DHS data [18]. There might be several reasons for employed women to experience terminated pregnancies compared to non-working women: decision-making power of working women regarding their reproductive health, prioritizing career goals over pregnancy, being more aware of contraceptive options including, menstrual regulation [18], or access to induced abortion through financial means [43] even though abortion is still illegal in Bangladesh.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations